Evaluation of the Turkey Nutrition and Health Surveys according to the mediterranean adequacy index and sustainability through water footprints - Nazlıcan Erdoğan Gövez; Şerife Akpınar Şentüre; Şerife Ayten; Eda Köksal (Cambridge University Press, 2023)
Abstract Objective: Sustainable diet is one of the main factors that support food security, and the Mediterranean diet (MD) one of the sustainable diet models associated with low ecological impact and optimum health results has come to the fore. It was aimed to compare the results of the 2010 and 2017 Turkey Nutrition and Health Studies (TNHS) according to the Mediterranean Adequacy Index (MAI) and in order to evaluate the environmental impact of the current nutritional status in Turkey through water footprints (WF). Design: The MAI score was calculated using the published results of the 2010 and 2017 TNHS, and the WF have been calculated as indicators of environmental impact. Setting: Turkey. Participants: There are no participants. Results: In the TNHS, there was an increase in the amount of energy provided by foods non-MD in 2017 compared to 2010, with a decrease in the total MAI score. The group with the lowest adherence to the MD in both years was the adult group (MAI20102·74 and MAI20172·31), while the group with the highest adherence was the adolescent group (MAI20103·21 and MAI20172·53). The MAI scores of females were higher than those of males in both years. The males aged 19-64 years had the largest (841 m3/year) WF and the females aged 65+ years had the smallest (483 m3/year). The food group that contributed the most to WF was meat and meat products (21·0-35·0 %). Conclusions: Adherence to the MD has decreased due to the increase in the consumption of the Western-type diet in Turkey.